2019
DOI: 10.1037/dev0000770
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ application of the virtues across five cultural contexts.

Abstract: Little is known about adolescent applications of the virtues such as honesty, responsibility and courage across different cultural contexts. Using the Adolescent Intermediate Concepts Measure we analyze samples of adolescents (ages 12 to 20; N ϭ 9,112) from 5 contexts: North Macedonia, Mexico, Taiwan, the United Kingdom, and the United States. Across samples, adolescents provide evidence of developmental growth in the ability to apply virtue concepts as assessed by responses to dilemma-based situations. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(52 reference statements)
0
7
0
2
Order By: Relevance
“…People spend considerable time in their waking hours reflecting upon and discussing moral dilemmas they face with their significant others and society at large (Narvaez, 2010). In many cases, that deliberation focuses on how to deal with conflicting considerations: for example, about how to respond to clashing demands of honesty and loyalty to friends (Thoma et al, 2019). The importance of deliberation clarifies why phronesis has historically attracted attention.…”
Section: First Section: Phronesis Redux and The New Model Of Wisdommentioning
confidence: 99%
“…People spend considerable time in their waking hours reflecting upon and discussing moral dilemmas they face with their significant others and society at large (Narvaez, 2010). In many cases, that deliberation focuses on how to deal with conflicting considerations: for example, about how to respond to clashing demands of honesty and loyalty to friends (Thoma et al, 2019). The importance of deliberation clarifies why phronesis has historically attracted attention.…”
Section: First Section: Phronesis Redux and The New Model Of Wisdommentioning
confidence: 99%
“…Walker, et al (2017) found that girls significantly outperformed boys in AD-ICM scores. Thoma, et al (2019) found gender differences in ICM scale scores favoring females across five cultural groups of participants in Macedonia, Mexico, Taiwan, the UK, and the USA. The possible explanations were:…”
Section: Different Characteristics Of the Three Groupsmentioning
confidence: 84%
“…There has also been a resurgence of scholarly interest in “character virtue development” which in some sense has reanimated the vision of Yeaxlee for an education that develops the “personality”—not in the sense of the stable traits of personality psychology as it since developed, but of “character” as a “dynamic relational system” (Lerner & Callina, 2014). Although a field with a confusing array of competing definitions and conceptual frameworks, arguably there is a growing evidence base for the notion of “character” and how it may be supported through educational interventions (Clement & Bollinger, 2016), for which there is some evidence for at least some intercultural norms (Thoma et al, 2019). In recent years, there has also been a surge of interest in related practices and their benefits for mental health, such as mindfulness (Van Dam et al, 2018).…”
Section: Pedagogies Of Spiritual Development and Their Basic Assumptionsmentioning
confidence: 99%